Desenho universal para aprendizagem na perspectiva da inclusão escolar: potencialidades e limites de uma formação colaborativa - Zerbato, Ana Paula (2018)
The scholarity of special education target public requires transformations in educational systems which include pedagogical practices designed for the successful learning of these students. In general, the teaching of these students, in the context of the common teaching classes, is specifically thought through accommodations, individualized adaptations of the curriculum, and flexibilizations. On the other hand, the Universal Design for Learning, aim to create means for the development of strategies for accessibility by all students, both in physical terms and in terms of services, resources and educational solutions, thereby they can learn without barriers. Considering the difficulty that teachers have in teaching students from the special education target public in common classes, the objective of the present study was to elaborate, to implement and to evaluate a collaborative training program on Universal Design for Learning. As a methodology, it was opted for the qualitative research with collaborative bias, because it was a joint form of the researcher and participants to produce knowledge about the educational context that they acted directly and, in the meantime, to contribute to the teacher training to face new educational challenges arising from the practices of school inclusion. The participants in the study were teachers of basic education who worked or had already had the experience of teaching students from special education target public in common teaching and undergraduate and graduate students. For data collection, different instruments were used: among them a characterization chart of the participants, teaching cases fictitious and real, a script for the orientation of the discussions and the evaluation form of the Training Program on Universal Design for Learning. The data collected were organized in thematic axes and the aim was to identify convergent and divergent points between the results of this research and the theoretical studies on the subject. It is hoped that this study will allow reflections on the proposals of school inclusion present in the common schools, helping in the elaboration of pedagogical practices that allow the participation and learning of all people and, therefore, to reduce the excess of individualization through private accommodations for the special education target students. It was also hoped to clarify the importance of the knowledge about the Universal Design for Learning for the initial and continuous formation of teachers in order to produce improvements in the teaching work within the perspective of the school inclusion.